Knowledge, Attitude, and Practice about Diabetes Mellitus and Its Implication on Oral Health among Diabetic Patients in Chengalpattu - A Cross-sectional Study - S. Saai Saranya; Karthikayan Ravi; Vishnu Prasad Subraman; K Indrapriyadharshini; Mahesh Jagadeson (Wolters Kluwer Medknow Publications, 2024)
Background Diabetes mellitus is considered to be a global epidemic. Currently india is considered to be the diabetic capital of the world. Despite the growing awareness of risk factors of diabetes mellitus and it's management, only few are aware of the oral health implications of diabetes mellitus. Aims and Objective With this background the study aims to assess the knowledge, attitude and practice about diabetes mellitus and its implication on oral health among diabetic patients. Materials and Methodology This cross-sectional study was conducted among 100 participants, who met the inclusion criteria, visiting the outpatient department of karpaga vinayaga institute of medical science. A self-administered was distributed among the participants. The questionnaire consisted of 19 closed questions which were divided into 3 domains: The first domain is knowledge of risk factors includes 5 questions; the second domain is attitude of diabetes mellitus patients includes 5 questions; the third domain is oral health related knowledge included 9 questions. Statistical analysis was performed using spss. Chi-square test was used to compare association between males and females in P value of <0.05 was considered to be significant. Results The results displayed that the participants had adequate knowledge about risk factors of diabetes mellitus and they also showed positive attitudes towards the management of diabetes mellitus. However, their knowledge regarding oral health complications of diabetes mellitus was not so high. Conclusion These results necessitate the implementation of various oral health and public health programs to increase people's knowledge and awareness of diabetes-related oral health conditions.